Analisis pengaruh pemberian virgin coconut oil (VCO) terhadap adhesi intraperitoneal - ., Erwin; Panelewen, Jimmy; Lahunduitan, Ishak (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: Intraperitoneal adhesion is an attachment between intraperitoneal tissue and organ in the form of fibrosis. The occurences of intraperitoneal adhesion are 67-93% after laparotomy and 97% after gynecological operation. Adhesion between wound and omentum occurs in 80% of patients; 50% involve the intestines. Prevention and inhibition of adhesion formation can be done by decreasing post traumatic inflammation. There are several substances that can be used for that purpose, inter alia: anti-inflammation, anti-histamine, anti-coagulant (heparin), anti-oxidant, proteolytic enzymes, and tissue plasminogen activator. It is already known that virgin coconut oil (VCO) has several important roles, such as: anti-inflammation, antithrombosis, mechanical barrier, and antioxidant due to its tocopherol content. This study aimed to obtain the influence of several doses of intraperitoneal VCO on intraperitoneal adhesion macroscopically and microscopically after laparotomy. This was an analytical interventional study using control. Samples were male Wistar rats (Rattus norvegicus) with an average body weight of 175-200 g. The results of Kruskal-Wallis chi-square tests were 16.381, df = 4, and Asymp sig = 0.003 (P < 0.05) for macroscopical grading (Zühlke) meanwhile 15.160, df = 4, and Asymp sig = 0.004 (P < 0.01) for microscopical grading (Yilmaz). Conclusion: There was a statistically significant difference in macroscopical grades according to Zühlke and in microscopical grades according to Yalmiz among the five groups concerning the occurence of intraperitoneal adhesion in Rattus norvegicus.Keywords: intraperitoneal adhesion, virgin coconut oil (VCO).Abstract: Adhesi intraperitonial adalah timbulnya perlengketan berupa fibrosis antara jaringan dan organ di dalam rongga abdomen. Kejadian adhesi intraperitoneal sekitar 67-93% setelah operasi laparotomi bedah dan mencapai 97% pada operasi ginekologi. Adhesi antara luka dan omentum terjadi pada 80% pasien dan sekitar 50% melibatkan usus. Untuk mencegah atau mengurangi pembentukan adhesi dapat dilakukan dengan menurunkan inflamasi pasca trauma melalui bahan atau obat anti-inflamasi, anti-histamin, anti-koagulan (heparin), anti-oksidan, enzim proteolitik, dan tissue plasminogen activator. Virgin Coconut Oil (VCO) telah diketahui berperan sebagai antiinflamasi, antitrombotik, barier mekanik, dan antioksidan dengan bahan aktif utama tokoferol. Penelitian ini bertujuan untuk mengetahui pengaruh VCO secara makroskopik dan mikroskopik terhadap adhesi intraperitoneal dengan menganalisis perbandingan dosis VCO yang diberikan intraperitoneal pada hewan coba tikus Wistar. Jenis penelitian ini analitik intervensional dengan kontrol. Hewan coba ialah tikus Wistar (Rattus norvegicus) yang diseragamkan berat badan 175-200 g, jenis kelamin jantan, dan variannya. Hasil uji Kruskal-Wallis chi-square ialah 16,381 dengan df = 4 dan Asymp sig = 0,003 (P < 0,05) untuk penilaian makroskopik (Zühlke) sedangkan nilai 15,160, dengan df = 4 dan Asymp sig = 0,004 (P < 0,01) untuk penilaian mikroskopik (Yilmaz). Simpulan: Terdapat perbedaan bermakna dalam derajat makroskopik menurut Zühlke dan derajat mikroskopik menurut Yilmaz pada ke-5 perlakuan dalam kejadian adhesi intraperitoneal pada Rattus norvegicus.Kata kunci: adhesi intraperitoneal, VCO